Association of 5-Hydroxytryptamine 3 Receptor Antagonists With the Prognosis of Liver Failure - Chen, Yuting; Sun, Jingkang; Fan, Xiude; Wang, Xiaoyun; Zeng, Lu; Zhang, Xiaoge; Zhang, Kun; Li, Na; Han, Qunying; Liu, Zhengwen (Frontiers in Pharmacology, 2021)
Liver failure is a severe clinical syndrome with high mortality. 5-Hydroxytryptamine 3 receptor antagonists (5-HT3RAs) can reduce liver damage in animal models. We investigated whether 5-HT3RAs may improve the prognosis of liver failure. We analyzed the 28-day and 90-day mortality of liver failure patients in relation to the use of 5-HT3RAs using data from a tertiary hospital in northwest China. According to the use of 5-HT3RAs, 419 patients with liver failure [46 acute, 93 sub-acute (SALF), 44 chronic, 236 acute on chronic (ACLF)] were divided into 5-HT3RA group (n=105) and control group (n=314). 5-HT3RAs were associated with decreased 28-day (HR 0.18, 95% CI 0.10-0.34, p<0.001) and 90-day (HR 0.21, 95% CI 0.13-0.33, p<0.001) mortality. After propensity score matching (PSM) (n=67 in each group), 5-HT3RAs were still significantly associated with reduced 28-day (HR 0.10, 95%CI 0.04-0.26, p<0.001) and 90-day (HR 0.16, 95%CI 0.08-0.31, p<0.001) mortality. 5-HT3RA group patients had significantly higher 28-day and 90-day survivals than controls both before and after PSM (all p<0.001). This study shows that 5-HT3RAs are associated with increased survival of liver failure patients and thus may be used to treat liver failure if the findings are confirmed by additional studies.